The Incidence And Severity Of Frey’s Syndrome After Parotidectomy: A Retrospective Study - Daloglu, Mustafa; Guney, Kenan (ENT Updates, 2019)
Objective: The aim of this study was to investigate the incidence and severity of Frey’s syndrome (FS) among parotidectomy patients and to assess the impact of parotidectomy sequelae on quality of life (QoL). Methods: In total, 43 patients (21 males, 22 females) who underwent parotidectomy were included in this study. Iodine-starch test was applied to identify the presence and the severity of FS. The results were evaluated using a previously described grading system. Patients’ perceptions of parotidectomy sequelae were graded to identify their impact on QoL and also if there is an association between the extent of parotidectomy, the time elapsed after surgery and the severity of symptoms. Results: FS was diagnosed in 18 (41.8%) patients, 10 of which (23.3%) reported having FS symptoms. Of all patients who were diagnosed with FS, 11 (61.2%) patients’ symptoms were classified as mild, whereas 7 (38.8%) were classified as severe. There was no significant correlation between the incidence of FS and the time between surgery and diagnosis, or the extent of parotidectomy. Among all symptoms reported by patients, FS was the sequelae that caused the most discomfort after parotidectomy. Conclusion: The negative impact of FS on QoL is restricted to cases with severe symptoms, the incidence of which is rare and independent of the extent of surgery. To avoid overtreatment, true incidence of FS remains to be identified in study samples from different centers. By this means, clinicians can make more accurate definitions for indications of preventive procedures as well as treatment approaches.